Avaliação moluscicida das plantas Pterodon emarginatus Vogel 1837, Magonia pubescens St. Hil, e Croton urucurana Baill 1864, sobre Biomphalaria glabrata (Say, 1818) e cercaricida sobre Schistosoma mansoni (Sambon, 1907) - CORRÊA, Marinês Conceição Rieth (2006)
The molluscicide and cercaricide action of the Pterodon emarginatus plants Magonia pubescens and Croton urucurana found in the Brazilian scrubland center-west region and in other Brazilian regions where the schistosomose is endemic was evaluated separately in laboratories The brute etanolic extracto obtained after the dilution in water were tested over the Biomphalaria glabrata snails intermediary host of Schistosoma mansoni The evaluation of the bioactivity was done from the initial concentration of 100ppm over adult snails and those ones which died in the adult phase had their concentrations reduced at 50 25 and 12.5ppm successively The molluscicide effect was evaluated over the snails development phasis over the laying of eggs and over the ovigery masses hatching The extracts that did not show bioactivity on 100ppm did not have their concentrations decreased The P emarginatus extract did not demonstrate bioactivity over the snails the laying of eggs the ovigery masses hatching and the liberation of cercaries Showing the cercaricide effect five hours after the start of the experiment whereas the controlling group survived for 36 hours over the same conditions The M pubescens extract demonstrated 100% of bioactivity on the four concentrations utilized and in all the snails development phasis with the exception of the ovigery masses hatching The cercaricide effect was 100% on the 100 and 50ppm concentrations within fifteen minutes 100% on 25ppm within 30 minutes and 100% on 12.5ppm within two hours whereas the controlling group survived for 36 hours at the same conditions With the C urucurana extract the bioactivity was of 26.6% on the 100ppm concentration within 24 hours of an exposition over adult snails On the 50 25 and 12.5ppm concentrations it was not showed bioactivity over the adult and young snails the laying of eggs and the ovigery masses hatching It was presented bioactivity with newly-developed snails on the three concentrations tested after 24 hours of exposition With the cercaries the deaths were observed from the fifteen minutes on the 100 and 50ppm concentrations two hours on 25ppm and five hours on 12.5ppm, and in the controlling group they survived 36 hours at the same conditions The snails which survived to the P emarginatus e C urucurana extracts showed an increasing on the laying of eggs number when compared to the controlling group